MICROINSURANCE PROGRAM FOR TRADE UNION MEMBERS IN CAMBODIA: PRICING AND FINANCIAL PROJECTIONS - Suan, Ivy DC; Pang-rey, Mia; Almazan, Rainier V. (Philippine Management Review, 2009)
In a previous paper (Almazan, Pang-Rey, & Suan, 2007), the authors designed a microinsurance program for trade union members in Cambodia. This paper aims to define the acceptable range of benefits and contributions for the members if they decide to enroll themselves in the said program. The contributions and benefits will be determined using actuarial methods to make sure that the proposed premium rates can cover both the costs and the benefits committed by the microinsurance program. To determine the feasibility of the program, we will examine future cash flows, where future actuarial liabilities are computed using actuarial techniques. Capitalization, reinsurance and investment of reserves will likewise be discussed.
Keywords: actuarial pricing, Cambodia, financial projections, microinsurance